Inequalities on mortality due to acute respiratory infection in children: A Colombian analysis. - Alvis-Zakzuk, Nelson Jose; Castañeda-Orjuela, Carlos; Díaz-Jiménez, Diana; Castillo-Rodríguez, Liliana; Cotes, Karol Patricia; Chaparro, Pablo; Paternina-Caicedo, Ángel José; Alvis-Guzmán, Nelson Rafael; De la Hoz, Fernando Pío (Biomédica: Revista del Instituto Nacional de Salud)
Introduction: Acute respiratory infections (ARI) are a leading public health issue worldwide. Objective: To explore the inequalities in ARI mortality rates in under-5, according to socioeconomic characteristics. Materials and methods: We conducted an ecological analysis to study inequalities at municipal level due to ARI mortality in children under 5 years. The data were obtained from official death records of the Departamento Administrativo Nacional de Estadística. The analysis of inequalities in the under-5 mortality rate (U5MR) included: 1) Classification of the population in different socio-economic strata, and 2) measurement of the degree of inequality. We used the ARI-U5MR as an outcome measurement. The mortality rates were estimated at national and municipal levels for the years 2000, 2005, 2010, and 2013. Rate ratios, rates differences, and concentration curves were calculated to observe the inequalities. Results: A total of 18,012 children under 5 years died by ARI in Colombia from 2000 to 2013. ARI- U5MR was greater in boys than in girls. During this period, an increase in the infant mortality relative gap in both boys and girls was observed. In 2013, the U5MR evidenced that for boys from municipalities with the highest poverty had a 1.6-fold risk to die than those in municipalities with the lowest poverty (low tercile). In girls, the ARI-U5MR for 2005 and 2013 in the poorest tercile was 1.5 and 2 times greater than in the first tercile, respectively. Conclusion: Colombian inequalities in the ARI mortality rate among the poorest municipalities compared to the richest ones continue to be a major challenge in public health.